Why Ref? Understanding sport officials` motivations to begin, continue, and quit - Hancock, D. J.; Dawson, D. J.; Auger, D. (Movement & Sport Sciences - Science & Motricité, 2015)
With attrition rates of 30%, organizations need to understand sport officials` motivations to become and remain officials rather than quit. The purpose of this study was to assess these motivations. Using questionnaire data from an existing survey, we categorized participants (n = 514) as interactors, monitors, and reactors. Sport officials were motivated to begin officiating for intrinsic and for the sport reasons. For continuing officiating, participants cited intrinsic and social motivations. Finally, interactors, monitors, and reactors cited lack of respect, too much stress, and lack of recognition, respectively, as their main beliefs for why sport officials quit. Practical recommendations are provided, which might assist sport governing bodies in recruiting and retaining sport officials.